Princess Jellyfish. 06 - Higashimura, Akiko (Kodansha Comics, 2017)
In order to save Amamizukan, the girls decide to put up an exhibition of their work. When the Jelly Fish dresses catch the eye of Asia's greatest fashion influencer, Kai, it's not only the dresses that the mogul wants--it's the designer herself. Tsukimi and the gang are about to get the massive break they need, but at what price...? Afraid that he may lose Tsukimi, Kuranosuke must come to terms with what his true purpose for starting Jelly Fish once was. Meanwhile, Shu learns of the heartbreaking history of Kuranosuke's mother, while Chieko's mother makes a discovery that seals the fate of Amamizukan...